CAN CORPORATE SOCIAL RESPONSIBILITY OF REGIONAL BANKS IMPROVE IMAGE AND COMPETITIVENESS? - Barkah; Maswadi (Tanjungpura International Journal on Dynamics Economics, Social Sciences and Agribusiness, 2021)
Cause Proximity (X) has a significant effect on Corporate Image (Y1) or Citra Bank Kalbar. The first hypothesis is proven or accepted. Thus a positive assessment of Cause Proximity CSR implemented by Bank Kalbar will increase the positive image of Bank Kalbar. Corporate Image (Y) has a significant effect on Purchase Intention Intention to Become a Customer of Bank Kalbar (Y2) in Pontianak. The second hypothesis is proven or can be accepted. Thus, the more positive the assessment of the Corporate Image (Y) will increase the intention to become a customer of Bank Kalbar. Cause Proximity of Bank Kalbar's CSR activities (X) has no significant effect on the intention to become a customer of Bank Kalbar. The third hypothesis is unproven or unacceptable. Thus, the proximity of the customer to the area where the Bank Kalbar social program is implemented does not affect the intention to become a customer of Bank Kalbar